The phenomenon of the Atang ceremony of the Bagos of Saytan, Pugo, La Union : towards a theological inquiry into its significance and relevance for Philippine contextual theology - Mendoza, Alvin B. (Quezon City : St. Andrew's Theological Seminary, 2001)
Guided by the Theological Education Fund's working principle or definition of contextualization, with the four-fold questions the researcher has in mind, this study attempts to explore the origin, nature, dynamics and theology of the atang ceremony of the Bagos in Saytan. Results of this endeavor will serve as specimen in doing contextual theology with primal religions in the Philippines.
A thesis presented to the Southeast Asia Graduate School of Theology in partial fulfillment of the degree Master of Theology, April 2001
Thesis (M.Theo.)-- Southeast Asia Graduate School of Theology